Perubahan nutrisi ikan asam pedas dalam retort pouch dengan variasi waktu sterilisasi - Mutma'innah, Mustika Nindiya; Maherawati, Maherawati; Rahayuni, Tri (Universitas Muhammadiyah Mataram, 2022)
Asam pedas is a soupy food with spices and the main ingredient is thick-fleshed river fish. This food has a low shelf-life, so it is necessary to apply sterilization technology. This research uses catfish as the main ingredient and retort pouch as packaging. This study aimed to determine the best sterilization time for catfish’s asam pedas using retort pouch packaging based on physicochemical and microbiological characteristics. The sterilization time used is 5, 10, 15, 20, and 25 minutes. Parameters observed were fat, protein, pH, thiobarbituric acid (TBA), texture, and Total Plate Count (TPC). The results showed that the sterilization time did not affect fat content, protein content, hardness level, TBA value, and the number of microbes, but the sterilization time significantly affected the pH value of catfish’s asam pedas packaged in retort pouches. Overall, the sterilization process carried out in this study did not change the physicochemical and microbyological characteristics of the catfish’s asam pedas. The best treatment in this study was a sterilization time of 25 minutes with a TPC value of 6.14 x 106 CFU/ml, the protein content of 11.89%, the hardness level of 178.81 gf, the pH value of 6.11, the fat content of 6.27%, and the TBA content of 0.19 mg malonaldehyde/kg.